2002
DOI: 10.1038/sj.onc.1205526
|View full text |Cite
|
Sign up to set email alerts
|

Multiple tristetraprolin sequence domains required to induce apoptosis and modulate responses to TNFα through distinct pathways

Abstract: Expression of the immediate early protein tristetraprolin (TTP) is induced by numerous stimuli, including tumor necrosis factor-alpha (TNFa). Evidence indicates that TTP limits production of TNFa and other cytokines by directly binding and destabilizing their mRNAs. This eect seems to require only the conserved TTP zinc ®nger region, and is characteristic of the related proteins TIS11b and TIS11d. TTP, TIS11b, and TIS11d each also induce apoptosis through the mitochondrial pathway analogously to certain oncoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
51
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 56 publications
6
51
1
Order By: Relevance
“…Consistent with the model that TTP/TIS11 proteins influence growth, survival, or apoptotic signals, we have determined that their constitutive expression at modest levels induces apoptosis through the mitochondrial pathway (31). We have also shown that TTP has diverged functionally from the other two TTP/TIS11 proteins, in that TTP alone dramatically sensitizes cells to the apoptotic stimulus of TNF␣ (31,32). This last finding suggests that TTP could contribute to the cellular decision between activation or apoptosis in response to TNF␣.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Consistent with the model that TTP/TIS11 proteins influence growth, survival, or apoptotic signals, we have determined that their constitutive expression at modest levels induces apoptosis through the mitochondrial pathway (31). We have also shown that TTP has diverged functionally from the other two TTP/TIS11 proteins, in that TTP alone dramatically sensitizes cells to the apoptotic stimulus of TNF␣ (31,32). This last finding suggests that TTP could contribute to the cellular decision between activation or apoptosis in response to TNF␣.…”
mentioning
confidence: 69%
“…Although the isolated TTP zinc finger region can mediate its effects on TNF␣ mRNA stability in transfection assays (16), we have observed that the TTP zinc finger region is incapable of inducing apoptosis or of sensitizing cells to TNF␣-induced apoptosis (32). Together with the zinc fingers, the TTP N-and C-terminal regions each contribute to induction of apoptosis, and the N-terminal region is specifically required to sensitize cells to TNF␣ (32).…”
mentioning
confidence: 97%
“…TTP binds to AREs from RNAs coding for immediate-early genes such as c-fos, interleukin-3, and TNF-␣ (39,44,46,47) and confers instability to these messages. TTP also has a physiological role in the induction of apoptosis (48). We report that TTP is expressed in HCA-7 cells, that its transcription is up-regulated with cell confluence, and that levels of its RNA vary inversely with those of the full-length COX-2 mRNA.…”
mentioning
confidence: 93%
“…Tritetraprolin (-3.0) is a TNF-␣-induced product that blocks TNF-␣ production by facilitating degradation of TNF-␣ mRNA (26). PKC interacting cousin of thioredoxin 2 (Ϫ2.5) is an inhibitor of two factors important for T cell activation: NF-B and AP1 (27).…”
Section: Molecular Characterization Of the Host Response At The Fs͞z mentioning
confidence: 99%